EFIKASI DIRI AKADEMIK SEBAGAI MEDIATOR DALAM HUBUNGAN ANTARA HUSNUDZAN DAN STRES AKADEMIK PADA MAHASISWA - Ai Nurhasanah; Lydia Freyani Hawadi (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
Academic stress is a problem experienced mostly by students including those who live in Islamic boarding schools. This condition happens because of the learning process presssure which can affects them physically and psychologically. Many previous studies examined a number of variables that can reduce academic stress, including the variables of academic self-efficacy and positive mindset. Husnudzan, a positive mindset in Islam, is considered to have an influence on various psychological aspects such as mental health, resilience, self-acceptance and anxiety. The method used in this study is a quantitative method by distributing the adaptation of the academic stress scale (SSI), the husnudzan scale and the academic self-efficacy scale (TASES). The validity and reliability scores are 0.922 and 0.959 for academic stress scale, 0.876 and 0.796 for husnudzan scale, also 0.905 and 0.951 for academic self-efficacy scale. Data analysis was carried out by conducting correlation and mediation analyses. A total of 80 undergraduate students from State Islamic University of Sunan Gunung Djati Bandung (UIN Bandung) participated in the study. The results demonstrated that husnudzan Â significantly correlated with academic self-efficacy (r = 0.480 and p<0.01). In contrast, there was no significant correlation not only on academic self-efficacy and stress academic r = -0.147 (p = 0.193) but also on husnudzan and stress academic r = -0.169 (p = 0.135). The mediation test results showed that academic self-efficacy could not mediate the relationship between husnudzan and academic stress with indirect effect score -0.0944 (BootLLCI = -0.3656 and BootULCI = 0.1986).Keywords: academic self-efficacy, academic stress, husnudzan